Report from the Region: The "Anti-Gender" Wave Contested: Gender Studies, Civil Society, and the State in Eastern Europe and Beyond*. Issue 1 (1st March 2019) - ,
Abstract : On 12 October 2018, without any public statement or explanation, the responsible Hungarian authorities removed the two-year MA degree program in gender studies, first accredited in Hungary in 2007 and overhauled in 2016, from the list of approved study programs. (Students currently enrolled in any such master's degree at any university in the country can finish their course of studies as usual.) For the MA degree program in gender studies established in 2017 at Eötvös Loránd University in Budapest, a state university and the largest university in terms of student numbers in the country, this equals abolition. For the two-year MA program in critical gender studies at Central European University (CEU) it means the loss of Hungarian accreditation, by which the degree was formally recognized in the European Union. This combines with the fact that CEU has lost the right to enroll new students into its US programs operated in Hungary, and more generally to operate in Hungary as an American institution (though this still is subject to legal encounters). Already in March 2017, at the time when the higher education reform was announced that would result in making CEU's continued operation in Hungary impossible, the government discussed a report on "a number of questions of the gender studies MA degree, " and representatives of the small Catholic coalition partner of the government led by Viktor Orbán's Fidesz/Hungarian Civic Alliance, the Christian Democratic People's Party, publicly denied the legitimacy of gender studies as an academic subject.